Kill the messenger South Africa, London, New York... - Callner, Marty; Gladstein, Randall; Chris Rock Productions (Firm); Funny Business Productions (Firm); Home Box Office (Firm); HBO Home Entertainment (Firm); Warner Home Video (Firm) (New York, NY HBO Video, 2009)
Comic superstar Chris Rock stars in his fifth solo stand-up performance. From three of Chris's international performances - at South Africa's Carnival City Casino, London's Carling Apollo Hammersmith, and New York's legendary Apollo Theater. He delivers his adults-only take on dozens of social, political and celebrity issues.
South Africa's Carnival City Casino -- London's Carling Apollo Hammersmith -- Harlem's Apollo Theater in New York.
Title from container.
Wide screen (16:9).
Editor, Michael D. Schultz.
Chris Rock.
Originally broadcast on HBO television in 2008.
Rating: TV-MA CHV rating: 18A.
Keywords: African American comedians -- Performances; African American wit and humor; Stand-up comedy; Comedy sketches; Monologue comique; Video recordings for the hearing impaired; Stand-up comedy routines; American wit and humor; Documentary films